The Locus Coeruleus‐Periaqueductal Gray GABAergic Projection Regulates Comorbid Pain and Depression - Yuan Gao; Xue Zhang; Xiao‐Juan Liu; Yi‐Ling Sun; Cui Yin; Dong‐Liang Tang; Cheng Xiao; Chunyi Zhou (Advanced Science, 2025)
Abstract The locus coeruleus (LC) noradrenergic (NA) neurons regulate pain and depression through their projections to various downstream nuclei. Although GABAergic (GABA) neurons in and near the LC (LC‐GABA neurons) provide inhibitory synaptic inputs to LC‐NA neurons, it remains unknown whether they are implicated in neuropathic pain and comorbid depression through LC‐NA neurons. This study demonstrates that LC‐GABA neurons respond to noxious stimuli with enhanced activity, and stimulation of these neurons elevates pain thresholds and exerts an anti‐depressant‐like effect in naive and neuropathic pain mice. Conversely, inhibition of LC‐GABA neurons leads to hyperalgesia and depression‐like behaviors in naive mice and exacerbates existing pain‐ and depression‐like behaviors in neuropathic pain mice. Although LC‐GABA neurons inhibit pain responses in LC‐NA neurons, they modulate pain thresholds and depression‐like behaviors in a manner independent of LC‐NA neurons. In contrast, the projection from LC‐GABA neurons to the ventrolateral periaqueductal gray (vlPAG) is enhanced, and stimulation of this projection mimics that of LC‐GABA neurons conferring analgesic‐ and antidepressant‐like effects. This study reveals the enhancement of the LCGABA‐vlPAGGABA projection as a compensatory mechanism in neuropathic pain and suggests that further augmentation of this projection may be a therapeutic strategy for the treatment of comorbid neuropathic pain and depression.